The growth performance of rock partridge (alectoris graeca) fed the diets with different protein level - Cavit Arslan; Mustafa Garip; Alper Yılmaz; Kemal Kırıkçı (Eurasian Journal of Veterinary Sciences)
This study was carried out to determine the effects ol different protein levels on growth characteristics in rock partridges. A total of 279 partridges were used in this study. Partridges were fed the diets with 16. 20 . 24. 28 % CP in 0-5 weeks. (Group I. II. ill. IV), and 14. 18, 22. 24 % CP in 6-9 weeks. At the end ol the research, live weight in groups were found to be 282.02, 333.38, 357.75 and 372.10 g respectively (P<0.001). As a result, depend on the increase of protein level in diets live weight and feed efficiency were increased.